Family ties: School assignment with siblings - Umut Mert Dur; Thayer Morrill; William Phan (Theoretical Economics, 2022)
We introduce a generalization of the school choice problem motivated by the following observations: students are assigned to grades within schools, many students have siblings who are applying as well, and school districts commonly guarantee that siblings will attend the same school. This last condition disqualifies the standard approach of considering grades independently as it may separate siblings. We argue that the central criterion in school choice - elimination of justified envy - is now inadequate as it does not consider siblings. We propose a new solution concept, suitability , that addresses this concern, and we introduce a new family of strategy-proof mechanisms where each satisfies it. Using data from the Wake County magnet school assignment, we demonstrate the impact on families of our proposed mechanism versus the "naive" assignment where sibling constraints are not taken into account.
Keywords: C78; D47; D63; I20; 330; School choice; matching theory; matching with contracts